Pemberian Topikal ASI Terhadap Resiko Infeksi Tali Pusat Neonatus: Studi Kasus - Perwiraningtyas, Pertiwi; Cahyaningrum, Ika; Leton, Elisabet Masan (Tribhuwana Tunggadewi University, 2024)
Inflammation of the umbilical cord is one of the triggers of morbidity and mortality in newborns worldwide. Various preventive and curative efforts are made to reduce this incident. This case study aims to improve the provision of nursing care for newborns with infection risk problems. A case study design was used in this study. The research subjects were selected using the accidental sampling method. The study was conducted on three neonates aged 7 days with the condition that the umbilical cord had not yet come off in the postpartum room of Dr. R. Soedarsono Pasuruan Hospital on February 23-28, 2022. The focus of the problem was the risk of infection. The intervention carried out on the umbilical cord using breast milk. The results of the study showed that the umbilical cords of all babies were wet on the first day. The application was by applying the base of the umbilical cord with a cotton bud that had been given 1-2 drops of breast milk, done 2 times in the morning and evening after bathing. After two days of treatment, the nursing problem of infection risk was resolved. This was indicated by the umbilical cord which tended to be dry and there were no signs of inflammation such as: no redness, odor, pus, edema, and tenderness. The results of this case study serve as a guideline for providing nursing care for newborns, especially those at risk of experiencing inflammation of the umbilical cord. Peradangan yang terjadi pada tali pusat menjadi salah satu pencetus morbiditas dan mortalitas bayi baru lahir di seluruh dunia. Berbagai upaya preventif maupun kuratif dilakukan untuk menekan kejadian tersebut. Studi kasus ini bertujuan sebagai upaya peningkatan pemberian asuhan keperawatan pada bayi baru lahir dengan masalah resiko infeksi. Desain studi kasus digunakan dalam penelitian ini. Subjek penelitian dilakukan dengan metode accidental sampling. Penelitian dilakukan terhadap tiga neonatus usia 7 hari dengan kondisi tali pusat belum terlepas di di ruang nifas RSUD dr. R. Soedarsono Pasuruan tanggal 23-28 Februari 2022. Fokus permasalahan adalah resiko infeksi. Intervensi yang dilakukan pada tali pusat dengan menggunakan ASI. Hasil penelitian menunjukkan tali pusat seluruh bayi dalam keadaan basah pada hari pertama. Penerapannya dengan mengoleskan pangkal tali pusat dengan cotton bud yang sudah diberi tetesan ASI sebanyak 1-2 tetes, dilakukan 2 kali pagi dan sore setelah mandi. Setelah perawatan selama dua hari, masalah keperawatan resiko infeksi teratasi. Hal ini ditandai dengan tali pusat yang cenderung kering dan tidak ada tanda-tanda peradangan seperti: tidak ada kemerahan, berbau, pus edema dan nyeri tekan. Hasil studi kasus ini, menjadi salah satu pedoman dalam pemberian asuhan keperawatan bayi baru lahir khususnya yang beresiko mengalami peradangan pada tali pusat